IMPLEMENTASI KARAKTER JUJUR, TOLERANSI, DISIPLIN DAN KREATIF SISWA KELAS V SDN 29 PONTIANAK KOTA - Fitri Geriyanti; Hery Kresnadi; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The research aims to describe the implementation of honest character, tolerance, discipline and creative and the inhibiting factors for the implementation of honest character, tolerance, discipline and creative class V in SDN 29 Pontianak Kota. This study uses data collection techniques such as observation, interviews and documentation. Data analysis using Miles and Huberman analysis techniques, namely data reduction, data display and conclusion drawing. Test the validity of the data using triangulation techniques and sources. The results showed that: (1) The implementation of honesty, tolerance, discipline and creative character education in class V at SDN 29 Pontianak Kota includes three aspects namely planning, implementation and evaluation. Planning is done by incorporating character education into the school's vision and mission and school rules. Implementation of honesty, tolerance, discipline and creative character by integrating self-development activities, subjects, and school culture, while the evaluation is done by attitude assessment. (2) The inhibiting factor of the implementation of honest, tolerance, discipline and creative character in class V SDN 29 Pontianak Kota consists of the first internal factor which is the lack of self-awareness of students. The two external factors, namely the social environment and the differences in culture at school with the culture at home. Keywords: Implementation, Character, Honesty, Tolerance, Discipline, Creative